ИССЛЕДОВАНИЕ АЛЛЕЛОХИМИЧЕСКИХ ВЕЩЕСТВ ДЫННОЙ МУХИ MYIOPARDALIS PARDALINA BIGOT - Джумакулов , Т (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
A method for the isolation and determination of allelochemical substances of the melon fly Myiopardalis pardalina Big. was studied; the GC-MS method was used for determination; it was carried out on an Agilent 8890 gas chromatograph; the amount of biomaterial was extracted with organic solvents.